Gust load alleviation of flexible composite wing - Ibren, Mohamed; Sulaeman, Erwin; Andan, Amelda Dianne; Aminanda, Yulfian; Halim, A. K. A (Penerbit Akademia Baru, 2020)
Gust load due to atmospheric turbulence is mandatory to be considered in aircraft analysis as part of airworthiness requirement. This safety related issue becomes more relevant recently in relation to the global warming that induces more frequent and extreme atmospheric disturbances encountered during air transportation. A direct application of gust load on the wing structural analysis, however, is not recommended since it will result in a significant weight increase due to the overdesign of the wing structure. At this point, the gust load alleviation plays an important role to effectively utilize the wing structural flexibility without ignoring the safety issue. In the present work, a method to alleviate the wing gust load is proposed by considering different configurations of the wing planform, wing sweep angle, wing dihedral angle and composite material layers. The objective of the study is to minimize the wing root bending moment due to the gust. The gust load analysis of the Kim-Hwang’s wing model will be used and the results are compared to the literature for the validation purpose. A finite element approach is used to simulate the wing structure in combination with the doublet lattice method to model the wing aerodynamics. It is found that the wing dihedral angle plays insignificant changes to the wing root bending moment due to the gust load. The wing sweep angle, however, gives significant changes to the wing root bending moment. For the present configuration, the optimum swept back configuration with a 45° sweep angle and optimum composite lay-up showed an average decrease of the bending moment by 12% for frequency range of 0 to 100 Hz. © 2020 PENERBIT AKADEMIA BARU.